Iridescent Daytime Radiative Cooling with No Absorption Peaks in the Visible Range. Issue 25 (19th May 2022) - Ding, Zhenmin; Pattelli, Lorenzo; Xu, Hongbo; Sun, Wenhai; Li, Xin; Pan, Lei; Zhao, Jiupeng; Wang, Chengyu; Zhang, Xiang; Song, Ying; Qiu, Jun; Li, Yao; et al.
Abstract: Coatings for passive radiative cooling applications must be highly reflected in the solar spectrum, and thus can hardly support any coloration without losing their functionality. In this work, a colorful daytime radiative cooling surface based on structural coloration is reported. A designed radiative cooler with a bioinspired array of truncated SiO2 microcones is manufactured via a self‐assembly method and reactive ion etching. Complemented with a silver reflector, the radiative cooler exhibits broadband iridescent coloration due to the scattering induced by the truncated microcone array while maintaining an average reflectance of 95% in the solar spectrum and a high thermal emissivity (ε) of 0.95, owing to the reduced impedance mismatch provided by the patterned surface at infrared wavelengths, reaching an estimated cooling power of ≈143 W m –2 at an ambient temperature of 25 °C and a measured average temperature drop of 7.1 °C under direct sunlight. This strong cooling performance is attributed to its bioinspired surface pattern, which promotes both the aesthetics and cooling capacity of the daytime radiative cooler. Abstract : The designed radiative cooler consists of a bioinspired amorphous structure made of SiO2 microcones obtained by reactive ion etching of the SiO2 substrate. This iridescent radiative cooler exhibits broadband iridescent coloration due to the scattering induced by the truncated microcone array while achieving efficient solar reflection (95%) and long‐wave infrared emission (0.95) without visible absorption peaks.